Implementation of Expository Learning Integrated with Active Students Learning Strategy to Improve Learning Outcomes in Stoichiometry - Ion Wijaya; Muchlis Muchlis; Ariwati Wahyu Mumpuni (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Stoichiometry material is often still considered difficult for students in learning chemistry, causing low learning outcomes. This study aims to determine the effect of integrating the Expository Learning with the Active Student Learning  on student learning outcomes in stoichiometry material in class X-4 SMA Negeri 1 Kediri. This research involved 36 students of class X-4 SMA Negeri 1 Kediri as research subjects. This research used classroom action research method with two cycles. The results showed an increase in the average learning outcomes of students. Before the research (T0), the average score was 65.33, categorized as low, with a learning completeness rate of 55.56%. In cycle 1 (T1), the average score increased to 80.56, classified as good, with a learning completeness rate of 75%. In cycle 2 (T2), the average score increased to 88.47, classified as very good, with a learning completeness rate of 88.89%. Based on these results, the integration of the expository learning with active student learning can be considered for use in students who have a low understanding of chemical concepts in order to improve their learning outcomes on stoichiometry material.